Strategic Gamification in Communication: Enhancing Engagement in Learning and Health Sectors - Toun, Nicodemus R. (Indonesian Scientific Publication, 2024)
Gamification has emerged as a powerful approach in enhancing communication strategies across various domains, including education, health, and public advocacy. This narrative review explores how gamification influences engagement, knowledge retention, and behavioral change through communication. A comprehensive literature search was conducted across databases such as Scopus, Web of Science, PubMed, and Google Scholar using Boolean keyword combinations including